Learning and Stroke Recovery: Parallelism of Biological Substrates - Joy, Mary Teena; Carmichael, S. Thomas (Seminars in Neurology, 2021)
Stroke is a debilitating disease. Current effective therapies for stroke recovery are limited to neurorehabilitation. Most stroke recovery occurs in a limited and early time window. Many of the mechanisms of spontaneous recovery after stroke parallel mechanisms of normal learning and memory. While various efforts are in place to identify potential drug targets, an emerging approach is to understand biological correlates between learning and stroke recovery. This review assesses parallels between biological changes at the molecular, structural, and functional levels during learning and recovery after stroke, with a focus on drug and cellular targets for therapeutics.
Keywords: stroke; learning and memory; neurorehabilitation; dendritic spines; axonal sprouting; molecular systems; cortical maps; functional motor recovery